Vegetation composition and diversity in the habitats of Kikuyu grass (Pennisetum clandestinum) in West Java highlands, Indonesia - SARI SURYANAH; IMAN HERNAMAN; MANSYUR MANSYUR; AGUNG KARUNIAWAN; DEDI RUSWANDI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Suryanah S, Hernaman I, Mansyur, Karuniawan A, Ruswandi D. 2025. Vegetation composition and diversity in the habitats of Kikuyu grass (Pennisetum clandestinum) in West Java highlands, Indonesia. Biodiversitas 26: 5659-5670. Pennisetum clandestinum (Kikuyu grass) has the potential to be developed as pasture to feed livestock, yet it has the risk to be invasive, which might threaten native biodiversity. This study aimed to explore the ecology of Kikuyu grass in its habitats in highland areas across West Java, Indonesia. Vegetation analysis was conducted to examine the composition, structure, and diversity of plant communities in several of its habitats, thereby providing data on the vegetation coexisting with Kikuyu grass to infer whether this grass is invasive. A nested sample plot method was used to calculate the Importance Value Index (IVI) of all species and the biodiversity indicators for each plant habitus. The exploration recorded 18 accessions of Kikuyu grass in the highland areas (>1,000 m asl) in the districts of Bandung, West Bandung, Garut, and Subang. A total of 3,474 herbaceous plants (58 species, 19 families), 207 shrubs (20 species, 14 families), and 133 trees (11 species, 8 families) were recorded across the studied sites. The highest IVI for herbaceous species was Axonopus compressus (30.44%), shrub species was Chromolaena odorata (27.87%), and tree species was Pinus merkusii (117.49%). Analysis of biodiversity indices revealed that the research locations exhibited considerable floristic diversity (H′: 1.79-2.90), with a high evenness index (E: 0.71-0.85) and low dominance (D: 0.09-0.22) for all plant habitus. The species richness for herbaceous habitus was classified in the high category (R: 6.99), the moderate category (R: 3.56) for shrub habitus, and the low category (R: 2.04) for tree habitus. The highlands of Bandung District have an ideal ecological condition and vegetation community structure to support the natural growth of Kikuyu grass, characterized by balanced, stable, and species-rich vegetation. The study found that Kikuyu grass did not outcompete local species, indicating minimal ecological risks. These findings help identify suitable habitats for Kikuyu grass cultivation and provide valuable vegetation data for forage development efforts.